The importance of natural land carbon sinks in modelling future emissions pathways and assessing individual country progress towards net-zero emissions targets - van der Ploeg, Robin; Haigh, Martin (Frontiers in Environmental Science, 2024)
The United Nations Framework Convention on Climate Change (UNFCCC) land carbon accounting methods currently incorporate all CO2 fluxes on managed land in country inventories without distinguishing between anthropogenic and natural components, although efforts have been made to reconcile these differences in historical datasets. Meanwhile, uncertainties remain regarding the resilience of land ecosystems and their capacity to store increasing amounts of carbon under progressive global warming. Here we present a simple yet novel methodology to evaluate the present and future progression of natural land sinks at the regional and country level, developed in the context of the Shell Energy Security scenarios. Forests dominate the uptake of CO2 on land and as such, our analysis is based on allocating global projections of the natural land carbon flux from MIT's earth system model simulations to countries using a compilation of forest land areas for a historic and scenario range spanning 1960-2100. The resulting dataset enables an integrated comparison between anthropogenic and natural land carbon fluxes, and thus better evaluation of country NZE targets, for use in energy outlooks such as the Shell scenarios. Our combined anthropogenic and natural land carbon flux results for individual countries and regions such as the European Union (EU) show generally good agreement with recent independent estimates from recent land-use harmonisation studies for 2000-2020. This suggests that our workflow may be used for direct first-order exploration of future natural land fluxes at country level - a pathway that other studies do not yet offer. Our total net land carbon fluxes based on combined anthropogenic and natural land fluxes show a reasonable first-order agreement for the largest countries, but the comparison also suggests that the apportionment of anthropogenic land-use emissions to use as an input to scenario models, such as the Shell World Energy Model (WEM), may be further improved. Given the importance of land carbon emissions and stocks, and the need to distinguish anthropogenic from natural changes so as to track appropriate targets, we recommend that the carbon cycle modelling and energy modelling research communities continue to collaborate to develop a next generation of relevant data products.